The impacts of international trade on global greenhouse gas emissions: A thought experiment based on a novel no-trade analysis. (15th December 2021) - Wu, Zhaodan; Yang, Lan; Chen, Qiyong; Ye, Quanliang
Abstract: Trade has been substantially influencing regional economic development, environmental sustainability, and human well-being. Enabled by the decomposition analysis, pollution haven hypothesis or "no-trade" scenarios (NTSs), the effects of trade on global/national social-economic-environmental development have been revealed. However, major limitations (e.g., using with-trade economic structures or neglecting price differences) existed in previous studies, and thus made the previous assessments of trade's effects unsatisfactorily. This study develops a novel NTS that addresses the existing limitations, and further applies it to estimate the effect of trade on global economic development and greenhouse gas (GHG) emissions. We show that current international trade benefits the global economic growth but with a consequence of more GHG emissions compared with the NTS. The hypothetical production in small countries (e.g., Luxembourg or Japan) would be more constrained by the production factors (e.g., land) under the NTS, compared with those factor-endowment countries (e.g., the United States or India). For country-specific analysis, we find that today's developed countries would have a substantial increase in their GHG emissions of clothing- and service-related products under the NTS, whereas countries with net-export (e.g., China or Brazil) would have less GHG emissions under the NTS. Enhancing future global collaborations is vital, especially for small or resource-deficient economies, if they are to achieve the Sustainable Development Goals. Highlights: A novel no-trade scenario (NTS) to address the limitations of existing NTS studies. Current international trade induces global economic growth with more GHG emissions. Economy and GHG emissions would recede in countries with limited production factors. Developed and current net-export countries would perform differently under the NTS. Enhancing the multi-lateral collaborations is suggested towards sustainability.